Pengaruh Partisipasi Anggaran, Kualitas Sumber Daya Manusia dan Komitmen Organisasi Terhadap Kinerja Manajerial Sekolah Luar Biasa (SLB) Pada Provinsi Maluku - Yaban, Nadine Emanuela Carolina; Dewi, Maya Widyana; Kristiyanti, LMS (Nur Science Institute, 2025)
This study aims to examine the influence of budget participation, human resource quality, and organizational commitment on managerial performance in Special Schools (SLB) in Maluku Province. A quantitative approach was applied, with data collected through questionnaires from 78 respondents and analyzed using multiple linear regression. The findings reveal that budget participation, human resource quality, and organizational commitment have a positive and significant effect on managerial performance, both individually and collectively. Human resource quality emerged as the most dominant factor, highlighting that competence and skills of educational staff are essential to improving school management effectiveness. These results emphasize the importance of strengthening participatory budgeting, enhancing human resource capacity, and fostering organizational commitment as strategic efforts to improve managerial performance in special education institutions.